2019
DOI: 10.21203/rs.2.9715/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Class 1 Integron and Antibiotic Resistance Pattern in Pseudomonas aeruginosa Isolated from Iranian Clinical Specimens; a Systematic Review and Meta-Analysis

Abstract: Background The role of integrons has been shown in the horizontal transmission of antibiotic resistance genes among bacterial isolates especially Gram-negative microorganisms in clinical settings. Objectives The aim of this study was to systematically review the prevalence of class 1 integrons and antibiotic resistance in Pseudomonas aeruginosa isolates of clinical samples of Iranian patients. Methods The Web of Science, PubMed, Scopus, and Science Direct databases were searched using preferred keywords based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
1
1
Order By: Relevance
“…Still, none of the imipenem-resistant P. aeruginosa isolates harbored an insertions element in the OprD gene. As shown by several studies, alteration of OprD increases the MIC for imipenem but not other carbapenems (38,50). A different study by Wolter et al showed the presence of IS elements within the OprD gene, which was not observed in this study (51).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Still, none of the imipenem-resistant P. aeruginosa isolates harbored an insertions element in the OprD gene. As shown by several studies, alteration of OprD increases the MIC for imipenem but not other carbapenems (38,50). A different study by Wolter et al showed the presence of IS elements within the OprD gene, which was not observed in this study (51).…”
Section: Discussioncontrasting
confidence: 59%
“…Among the present study's 80 clinical isolates of P. aeruginosa, 20% were resistant to carbapenems. The resistance range of P. aeruginosa to imipenem in other studies in different regions was 5.5 to 62.5% (25,(35)(36)(37)(38). Resistance to carbapenems in P. aeruginosa occurs via several mechanisms.…”
Section: Discussionmentioning
confidence: 95%